Spousal Interrelations in Self-Reports of Cognition in the Context of Marital Problems - Strawbridge, William J.; Wallhagen, Margaret I.; Shema, Sarah J. (Gerontology (Basel), 2011)
Background: Problems with cognitive function are common among older adults, yet there is little research assessing the extent to which the cognitive problems of older husbands and wives are related to those of their partners and whether any observed relationships are moderated by gender or marital quality. Objectives: Our purpose was to analyze longitudinal relationships between older spouses’ cognitive function and the cognitive function of their partners 5 years later, as well as to assess moderating roles of gender and marital quality. Methods: The subjects were 378 community-dwelling couples aged 46–89 years at baseline who were followed for 5 years. Cognitive function was measured with a scale assessing problems remembering names, finding the right word, misplacing things and paying attention. Marital quality was assessed by comparing those reporting marital problems often or sometimes with those reporting marital problems rarely or never. All data were collected by self-report. Statistical models adjusted for paired data where appropriate and included partner cognitive function, age, chronic conditions and financial hardship. Stratified models assessed moderating roles of gender and marital problems. Results: We found a negative relationship between husbands’ baseline lower cognitive function and wives’ subsequent cognitive function but only for the wives reporting marital problems. We found no comparable relationship between wives’ baseline lower cognitive function and their husbands’ subsequent cognitive function. Conclusions: Our gender-specific finding for wives is consistent with the gender differences noted in 2 previous studies. The limitation to wives with problems in their marriages is a new finding and might follow increased stress and depression responding to changes in their husbands’ cognitive functioning.